Impact of Fish Population Density on Growth and Production of Sarpunti, Mrigal and Tilapia in Polyculture System - Chowdhury, SN; Paul, M; Barman, AC; Bhadra, A; Rahman, MS (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted to determine the impacts of fish population density on the growth and production of sarpunti (Barbonemus gonionotus), mrigal (Cirrhinus mrigala) and tilapia (Oreochromis niloticus) in polyculture system for a period of 90 days in six earthen pond .The experiment was carried out under three treatments each with two replications. The stocking density was 50 fish per decimal (sarpunti 20, mrigal 20 and tilapia 10) under treatment-I, 75 fish per decimal (sarpunti 30, mrigal 30 and tilapia 15) under treatment-II and 150 fish per decimal (sarpunti 60, mrigal 60 and tilapia 30) under treatment- III and all the ponds under three treatments supplementary feed was not used. The average initial length and weight of the fingerlings of sarpunti, mrigal and tilapia were 13.29 cm, 12.80 cm, 4.55cm and 22.7g, 23.75g and 3.84 g respectively. The ponds were fertilized fortnightly with cowdung, urea and TSP at the rates of 5 kg, 100 g and 200g per decimal, respectively. Mean survival rates of fish under treatment-I, treatment-II and treatment-III were 87.50%, 88.16% and 81.30% respectively. The specific growth rates (SGR, % per day) of fish under treatment-I, treatment-II and treatment-III were 1.13%, 1.03% and 0.80%. The calculated net fish production of the ponds under treatment-I was 1.61 ton/ha/yr and that of the ponds under treatment-II was 1.97 ton/ha/yr and 2.5 ton/ha/yr in treatment-III. DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22095 J. Environ. Sci. & Natural Resources, 6(2): 49-53 2013